What outcomes are important in the recovery from acromio-clavicular (AC) joint pathology? A focus group study with patients and surgeons. Issue 10 (8th May 2022) - Aldhuhoori, Saif; Almasri, Mahmoud; Nicholls, Stuart G.; Pollock, J. Whitcomb; Rollins, Meaghan; Howard, Lisa; Lapner, Peter
Abstract: Introduction: Acromio-clavicular (AC) joint pathology is a disabling condition that can restrict quality of life through chronic pain and functional limitation. The objective of this study was to determine symptoms and patient-centred outcomes identified by patients with AC pathology and from experienced shoulder surgeons. Methods: Qualitative research methods were undertaken with patient and surgeon focus groups. Patients with AC-joint pathology were invited to participate and were stratified into two cohorts: AC instability and AC osteoarthritis (OA). Results: Sixteen patients participated in five patient focus group discussions including 10 patients with AC instability and six patients with AC OA. Four surgeons participated in two focus groups. Although some themes were common to both AC Instability and AC OA, a number of themes were unique to each. A number of themes were identified that do not appear in existing AC joint scores. Conclusion: Although many factors affecting the AC joint were common to instability and OA pathology, several factors appear to be unique to each and do not appear in existing AC joint metrics. These symptoms and patient-centered outcomes may be used by clinicians in the assessment of patients with AC pathology and in the development of rehabilitation programs. Implications for rehabilitation: A thorough understanding of symptoms and patient-centred outcomes associated with acromio-clavicular arthritis and instability is necessary in order to conduct an accurate clinical assessment and design an effective rehabilitation program that meets the clinical needs of patients. Patients in this study identified several themes relevant to assessment and rehabilitation program development including pain location, type of pain (eg. burning pain), and specific activities that induced pain that do not exist in current existing tools. Our finding that certain themes were only raised in either acromio-clavicular instability or osteoarthritis suggests that there may be differences in important outcomes for patients depending on the underlying cause of the acromio-clavicular joint pathology. By incorporating these themes into clinical assessments, outcomes important to patients may be elicited to monitor response to rehabilitation following injury or surgery.